ANALISIS PENERAPAN PRINSIP-PRINSIP KOPERASI DALAM UNDANG-UNDANG KOPERASI (Studi Undang-Undang No. 25 Tahun 1992 dan Undang-Undang No.17 Tahun 2012) - Aji Basuki Rohmat (UNISSULA, 2015)
Studied law build cooperative efforts very closely related to the economic system adopted by a State, because the legal build cooperative efforts is to learn about the ideology, ideology andeconomic system adopted by the State. Implementation of the application of the Act cooperative must pay attention to the development of co-operative principles are applied internationally, in this case the cooperative principles set out the International Cooperative Alliance and other business practices. This study uses normative juridical approach, in which the specification of research using descriptive analysis that researchers seek will describe the application of the principle of cooperation in an Act. The results obtained show that Law No.25 of 1992 on Cooperatives have applied the principles of cooperative and is in conformity with Article 33 paragraph (1) and paragraph (4) of the Constitution of 1945. In order to repair and renewal of cooperative law , Cooperative Act 25 of 1992 in 2012 renewed by Act 17 of 2012. However, Act 17 of 2012, by most practitioners and cooperative actors considered incompatible with the cooperative identity, so is referred Judicial Review as to Law 17 of 2012 to the Constitutional Court. In its decision the Constitutional Court annul the Cooperative Act 17 of 2012, Since the Act 17 of 2012 is contrary to Article 33 paragraph (1) and (4) of the Act of 1945